Asian-American Variants of Human Papillomavirus 16 and Risk for Cervical Cancer: a Case–Control Study - Berumen, Jaime; Ordoñez, Rosa M.; Lazcano, Eduardo; Salmeron, Jorge; Galvan, Silvia C.; Estrada, Ruth A.; Yunes, Elsa; Garcia-Carranca, Alejandro; Gonzalez-Lira, Guillermo; Madrigal-de la Campa, Angeles (JNCI : Journal of the National Cancer Institute, 2001)
Background: Human papillomavirus 16 (HPV16) has a number of variants, each with a different geographic distribution and some that are associated more often with invasive neoplasias. We investigated whether the high incidence of cervical cancer in Mexico (50 cases per 100 000 women) may be associated with a high prevalence of oncogenic HPV16 variants. Methods: Cervical samples were collected from 181 case patients with cervical cancer and from 181 age-matched control subjects, all from Mexico City. HPV16 was detected with an E6/E7 gene-specific polymerase chain reaction, and variant HPV classes and subclasses were identified by sequencing regions of the E6 and L1/MY genes. Clinical data and data on tumor characteristics were also collected. All statistical tests were two-sided. Results: HPV16 was detected in cervical scrapes from 50.8% (92 of 181) of case patients and from 11% (20 of 181) of control subjects. All HPV16-positive samples, except one, contained European (E) or Asian-American (AA) variants. AA and E variants were found statistically significantly more often in case patients (AA = 23.2% [42 of 181]; E = 27.1% [49 of 181]) than in control subjects (AA = 1.1% [two of 181]; E = 10% [18 of 181]) (P<.001 for case versus control subjects for either E or AA variants, χ2 test). However, the frequency of AA variants was 21 times higher in cancer patients than in control subjects, whereas that ratio for E variants was only 2.7 (P = .006, χ2 test). The odds ratio (OR) for cervical cancer associated with AA variants (OR = 27.0; 95% confidence interval [CI] = 6.4 to 113.7) was higher than that associated with E variants (OR = 3.4; 95% CI = 1.9 to 6.0). AA-positive case patients (46.2 ± 12.5 years [mean ± standard deviation]) were 7.7 years younger than E-positive case patients (53.9 ± 12.2 years) (P = .004, Student's t test). AA variants were associated with squamous cell carcinomas and adenocarcinomas, but E variants were associated with only squamous cell carcinomas (P = .014, Fisher's exact test). Conclusions: The high frequency of HPV16 AA variants, which appear to be more oncogenic than E variants, might contribute to the high incidence of cervical cancer in Mexico.